ANALISIS PENINGKATAN KREATIVITAS ANAK MELALUI KEGIATAN KOLASE MENGGUNAKAN BAHAN ALAM PADA KELOMPOK B DI PAUD - Ismawati; Sormin, Darliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creativity development in early childhood requires learning activities that provide opportunities for children to explore, make choices, and express ideas through meaningful experiences. Initial observations in Group B at PAUD Faza Azkia and TK Cerdas, South Tapanuli, indicated that some children tended to imitate teachers’ examples, depended on guidance, and had limited opportunities to develop their own ideas. This study aimed to analyze the development of children’s creativity through collage activities using natural materials. The study employed a descriptive qualitative approach involving 30 children from Group B, consisting of 15 children from PAUD Faza Azkia and 15 children from TK Cerdas. Data were collected through observation, semi-structured interviews, and documentation conducted from April to July 2026. Data validity was established through source and technique triangulation, while data were analyzed through data condensation, data display, and conclusion drawing and verification. The findings indicated that collage activities using natural materials provided opportunities for children to explore materials, generate ideas, combine materials flexibly, produce unique works, add details, and complete their work more independently. The development of creativity was particularly evident in fluency, flexibility, originality, and elaboration. The teacher’s role as a facilitator through open-ended questions, freedom of choice, appropriate assistance, and appreciation also supported children’s creative development. The study concludes that collage activities using natural materials can serve as an alternative art-based learning activity to stimulate creativity in early childhood education.